Interpretaciones humanísticas de un tópico clásico: el poema a la muerte de un ave (I) : el "Epitaphium Parrochini sturni" de Maffeo Vegio - Díaz Gito, Manuel Antonio (Calamus Renascens: revista de humanismo y tradición clásica, 2001)
The aim of our study is the analysis of the different treatment of a well-known classical topic in the tradition of the Roman erotic poetry, the poem to the death of a pet-bird, by two representative Italian humanists of the Quattrocento, Maffeo Vegio and Giovanni Pontano. In this paper we present a first part of this study focused on the Epitaphium Parrochini sturni by Maffeo Vegio.